2014
DOI: 10.1097/ede.0b013e31828ac01b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Waves on Mortality

Abstract: The heat wave effect on mortality was larger during high ozone or high PM10 days. When assessing the effect of heat waves on mortality, lack of adjustment for ozone and especially PM10 overestimates effect parameters. This bias has implications for public health policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(76 citation statements)
references
References 41 publications
2
71
2
1
Order By: Relevance
“…Recent studies have revealed significant interactions between ozone, PM 10 , and extreme heat (Analitis et al 2014) and extreme cold (Cheng and Kan 2012) on the overall mortality. The earlier studies have associated outpatient visits for chronic pulmonary diseases mainly with ambient levels of O 3 and NO 2 instead of PM 10 (Yang et al 2007;Tsai et al 2006;Chan et al 2009;Lin et al 2013c).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed significant interactions between ozone, PM 10 , and extreme heat (Analitis et al 2014) and extreme cold (Cheng and Kan 2012) on the overall mortality. The earlier studies have associated outpatient visits for chronic pulmonary diseases mainly with ambient levels of O 3 and NO 2 instead of PM 10 (Yang et al 2007;Tsai et al 2006;Chan et al 2009;Lin et al 2013c).…”
Section: Discussionmentioning
confidence: 99%
“…There is a potentially interactive effect of high temperatures and pollutant concentrations (98100). Although there have been studies that have not detected evidence that increasing temperature modifies the effect of pollution exposure (101103), several studies have detected interactive effects (104108).…”
Section: Indoor Air Pollution and Copdmentioning
confidence: 99%
“…Studies that have included respiratory specific outcomes have also had conflicting results. For example, studies in China and Europe suggest an interactive effect of increases in temperature and pollution on the risk for cardiac death but not respiratory death (100, 109). A study in Brisbane, Australia did not suggest effect modification for respiratory emergency visits but demonstrated an interactive effect of increasing temperature and PM 10 on respiratory hospitalizations (110).…”
Section: Indoor Air Pollution and Copdmentioning
confidence: 99%
“…The effects of gender on temperature impacts have seen mixed evidence [12,13]. At the community level, vulnerability of populations has been shown to be influenced by factors such as low density of green spaces [15], poor urban design and planning [16], urban heat islands [17], and the modification effect by air pollutants [18,19]. Ozone in particular has been studied as an effect modifier in the mortality-temperature relationship [20,21], while the link between temperature and particulate matter (PM) [22], sulfur oxides (SOx) [23] or Nitrogen oxides (NOx) [24] has been less explored.…”
Section: Introductionmentioning
confidence: 99%